Pelatihan English Speaking bagi Siswa dengan Model Pembelajaran Presentation Practice Produce (PPP) - Baiq Sumarni; Dira Permana; Imansyah Imansyah; K Dedi Sandiarsa (Jurnal Pengabdian UNDIKMA, 2022)
This community service was aimed at improving English speaking ability using learning model of Presentation Practice Produce (PPP) for students of MA Al-Istiqomah Telaga Waru. This community service used learning model that is Presentation, Practice, Product (PPP) using cue response drill technique. Evaluation was conducted by giving speaking test to the participants to know whether or not the target of program is achieved. And to knowing whether this program has running well based on the procedure, observation rubric was also has been filled by the team when the program is in progress. The result of this training could increase students’ speaking ability. Based on the result of speaking test, students’ speaking ability have increased. The result of speaking test as the final evaluation, there are 15 out of 20 students got score  ≥ 70 or (77.37%). Thus, it could be said that this program was successful because more than 75% students got target score ≥ 70. This community service could increase students’ motivation and also it became one of the learning model that could be used by English teacher.  The response of the audience reveals that the program gave some good advantages for the participants as they have higher motivation in trying to speak in English. The participants also expected that the same program is conducted in the near future.